Dobi Desa / Nurul Nadhirah Mohd Rosli … [et al.] - MOHD ROSLI, NURUL NADHIRAH; KAMARUL ZAMAN, NUR FATIEHAH; ZAINI, NUR AIN SYUHADA; MAT ROSLY, NUR ALIYAH (2020)
This project focuses on Dobi Desa laundry business. This business committed to provide highest quality, efficient and productive solution for laundry services. In the first part of the project, the general information of the business has been collected. Information is gathered through the interview session with the owner and online sources. Objective of the project is to work on the background, organizational structure, products and services that Dobi Desa provided. Next, we study about the technology used for the business, business, operational, and marketing strategy used by the business to promote their services to the customers. Lastly, we research about the company financial achievements regarding how they manage their financial as well as achievements gain from the financial management. In this case study, the strengths, weaknesses, opportunities and threats for this business were analysed using SWOT analysis. Thus, from the needs and demands from existing consumer of this business, we analysed and find a solution to overcome and to fulfil their needs in Consumer Trend Canvas (CTC) analysis